2016
DOI: 10.1002/rcm.7483
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput collagen fingerprinting of intact microfaunal remains; a low‐cost method for distinguishing between murine rodent bones

Abstract: RationaleMicrofaunal skeletal remains can be sensitive indicators of the contemporary ecosystem in which they are sampled and are often recovered in owl pellets in large numbers. Species identification of these remains can be obtained using a range of morphological criteria established for particular skeletal elements, but typically dominated by a reliance on cranial characters. However, this can induce biases under different environmental and taphonomic conditions. The aim of this research was to develop a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 48 publications
(58 reference statements)
1
64
0
Order By: Relevance
“…We used matrixassisted laser desorption/ionization mass spectrometry to determine the relative mass-to-charge (m/z) values of the tryptic digest peptides in each bone sample. By comparing these values with a library of known fauna, we identified bones to genus or species in some instance (27)(28)(29)(30)(31). We screened a total of 383 unidentified bone samples from Vindija Cave (levels G1, G3, and stratigraphic unit G1-G3).…”
Section: Methodsmentioning
confidence: 99%
“…We used matrixassisted laser desorption/ionization mass spectrometry to determine the relative mass-to-charge (m/z) values of the tryptic digest peptides in each bone sample. By comparing these values with a library of known fauna, we identified bones to genus or species in some instance (27)(28)(29)(30)(31). We screened a total of 383 unidentified bone samples from Vindija Cave (levels G1, G3, and stratigraphic unit G1-G3).…”
Section: Methodsmentioning
confidence: 99%
“…Although we have emphasised how promising this relatively new technique of species identification is, the taxonomic resolution remains the key limitation when compared with aDNA (although it is considerably greater than can be achieved using the other molecular and nonmolecular methods discussed above). Even though the method is typically capable of obtaining genus-level information, with elephantids being a notable previously known exception ), and to the species level with some (Rybczynski et al 2013;Buckley et al 2016), there were further limitations identified in this study in some lineages. In particular these were within the carnivores, particularly the feliformes of the order Carnivora, where distinction was only observed at the level of subfamily (e.g.…”
Section: Collagen Fingerprinting For Species Identificationmentioning
confidence: 96%
“…Figs S3-S7). The ancient material consisted of screening the 12 317 fragments from Jenkinson's 1980s excavations (reposited in Creswell Crags Heritage Centre) for which peptide fingerprints were obtained in Buckley et al (2016) following a similar but less damaging method (i.e. demineralization with 0.3 M HCl over 4 h).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations